Tuning the gate and the gear: The LRRC26 (γ1) subunit modulates intrinsic gating and voltage-sensor coupling of the BK channel - Felipe Echeverría; Antonio Peña-Pichicoi; Miguel Fernandez; Willy Carrasquel-Ursulaez; Juan P. Castillo; Osvaldo Alvarez; Ramón Latorre (Proceedings of the National Academy of Sciences, 2026)
Association of auxiliary subunits (β1-4 and γ1-4) with the pore-forming α subunit of the calcium- and voltage-activated potassium (BK) channel provides functional diversity. γ1 promotes a significant leftward shift in the voltage-activation curve, ensuring proper function of secretory glands and allowing BK channels to release K + at the cell’s resting Ca 2+ concentration. Given its physiological importance, it is crucial to elucidate the mechanisms of γ1 action. However, structural and functional studies have yielded conflicting conclusions regarding the modulation of BK channels by γ1. Here, using macroscopic, single-channel, and gating-current measurements, we demonstrate that at zero mV, γ1 increases 106-fold the equilibrium constant for the closed–open transition by destabilizing the channel’s closed state and enhancing coupling between the voltage sensor and the pore domain, without affecting voltage-sensor activation. These results suggest that γ1 not only increases the energetic coupling between the voltage sensors and the pore but also primarily enhances the channel-opening reaction.